The escalating global problem of accidental human-mediated transport of alien species: A case study using alien herpetofauna interceptions in New Zealand. (February 2023) - Pili, Arman N.; Tingley, Reid; van Winkel, Dylan; Maria, Lisa; Chapple, David G.
Abstract: The global problem of biological invasions will continue escalating, given inadequate biosecurity worldwide. Developing stringent biosecurity is hindered by the lacking essential information on the global flows of alien species, especially alien species accidentally transported and neglected by biosecurity due to inapparent economic significance. We provide evidence and new perspectives on the temporal, geographical, taxonomic, and transport sub-pathway dimensions of the global flows of neglected alien species, using alien amphibians and reptiles ("herpetofauna") accidentally transported to New Zealand as a case study (2610 records from 1929 to 2021). We decomposed and forecasted the alien herpetofauna transport frequency using locally-weighted smoothing and dynamic regression modelling. We explored geographical patterns of the alien herpetofauna origins and destinations, and explored temporal trends in species diversity. Finally, we analysed a species×transport sub-pathway network to elucidate the diversity of sub-pathways used by alien herpetofauna. Alien herpetofauna transport frequency is generally increasing, with fluctuations coinciding with changes in biosecurity and economic expansion and recessions. The most recent decline was during the COVID-19 recession, but we forecast transport to recover. Two hundred and forty-three alien herpetofauna worldwide arrived at ports of entry across New Zealand. Alien herpetofauna were accidentally transported through 13 sub-pathways, primarily as stowaways in 'personal effects and household goods', and in 'machinery, vehicles, and equipment'. Our study illuminates that neglected alien species' transport frequency, spatial extent of origins and destinations, species diversity, and accidental transport sub-pathways are hugely underestimated and dynamic. These crucial oversights in the global flows of alien species significantly impede biosecurity worldwide.